Law Enforcement Against Disseminers Of Dishonour Content On Social Media: Case study the distribution of recordings of caning processions in Aceh - Siregar, Friska Anggi; Yulis, Sari (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
Responding to the phenomenon of defamation during the execution of caning sentences, the Aceh Government limited the place where caning sentences were carried out from initially being carried out in public places and then being transferred to detention centres or correctional institutions. This rule is stated in Governor's Regulation Number 5 of 2018. The aim of moving the place of execution to a detention centre is to protect the rights of the convict so that it does not spread on social media. With the issuance of Gubernatorial Regulation no. 5 of 2018, of course there are legal implications regarding whether or not to record the caning procession. If caning is considered a disgrace, then those who spread caning can be charged under the ITE Law on defamation, but this phenomenon continues to occur and there are no calls from law enforcers to prohibit it. Thus, researchers feel it is necessary to examine the legal certainty regarding the dissemination of recordings of caning processions on digital media, and what the view of Islamic law is regarding the dissemination of recordings of caning processions on digital media. This research is entirely qualitative research (qualitative approach) using a normative juridical approach or library research. From the results of the research, it was concluded that there is no clear prohibition on the distribution of caning punishments either in the governor's regulation or in the qanun, so the law is permissible. The perpetrator also cannot be charged under the ITE Law because the execution is open to the public. However, victims may report to the authorities if they feel that the news conveyed does not match the facts or attacks their honour. This is also not prohibited in Islam, because it is classified as permissible backbiting, with the aim of making the perpetrators feel embarrassed and have a deterrent effect and warning for others.